Quranic Linguistic Miracles: Fundamental Vocabularies and Their Impact on Arabic Language Studies - Zulkifli, Abdul Salam; Zolmaily, Muhammad Akmal; Talib, Noor Husna; Bahjat, Mujahid Mustafa; Mohd Ramli, Abdul Basir Awang (Ijaz Arabi Journal of Arabic Learning, 2025)
The Quran’s role as a foundational sacred text in preserving and shaping the Arabic language makes it an essential resource for linguists, learners, and educators to enhance their understanding of Quranic Arabic. A key sūrah that captures the fundamental vocabulary and concepts of the Qur’ān is Sūrah Al-Baqarah. Through a literature review, researchers found no previous study on the collection of these words and the number of derivatives in their various contexts. Therefore, this study aims to highlight the fundamental vocabulary of the Qurʼān in this Sūrah, as it includes these words that are repeated at least 50 times throughout the Qurʼān. Through the qualitative approach and analyzing documents in primary dictionaries of al-Quran words, researchers gathered data by analyzing the frequency of the words semantically and comparatively. They counted their frequency with their different derivations using "al-Muʻjam al-Mufahras li-Alfāẓ al-Qurʼān al-Karīm". "Muʻjam al-Adawāt wa-al-Ḍamāʼir" was also used as an additional resource. The meanings of the words were later clarified using "Muʻjam alfāẓ al-Qurʼān al-Karīm". This study concluded that the fundamental words in Sūrah Al-Baqarah include verbs, nouns, and prepositions, with the number of occurrences of their most commonly used derivations amounting to 227 terms. The fundamental vocabulary in this collection represents a rich linguistic treasure and a substantial scientific resource. The findings contribute not only to understanding word roots, derivational morphology, and syntactic patterns. Thus, this research underscores al-Quran’s role as a foundational sacred text in preserving and shaping the Arabic language, making it an essential resource for linguists, learners, and educators to enhance their understanding of Quranic Arabic.